2022
DOI: 10.18185/erzifbed.1202053
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Different Roasting Methods on Some Properties of Walnut Kernels

Abstract: In this study, the effects of oven roasting and microwave roasting on some properties of walnut kernels were determined. Roasting methods at different oven temperatures (70, 100, and 130 ºC for one hour) and at different microwave powers (240, 535 and 830 W for 5 min) were applied to samples. Moisture ratio values, total phenolic compound, antioxidant activity, and oil yield of the roasted and unroasted products were discussed. The highest oil yield was determined in the high temperature oven roasting but t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…This variable is crucial because it affects the taste, texture, and shelf life of nuts. After drying, it was observed that either an increase in temperature or an increase in duration led to a decrease in moisture content (Elgin Kılıc and Cınar, 2019;Kutlu et al, 2022). Fresh hazelnut samples have a moisture content of 17.16%.…”
Section: Discussionmentioning
confidence: 99%
“…This variable is crucial because it affects the taste, texture, and shelf life of nuts. After drying, it was observed that either an increase in temperature or an increase in duration led to a decrease in moisture content (Elgin Kılıc and Cınar, 2019;Kutlu et al, 2022). Fresh hazelnut samples have a moisture content of 17.16%.…”
Section: Discussionmentioning
confidence: 99%